Knowledge and Attitude Related to Chemical Hazards Among Employees in Dental and Oral Hospital, Indonesia - Prasetio, Diki Bima; Prachaiboon, Tiwakron; Pramesti, Shinta Dwi Surya; Putri, Nasya Adelia; Sahiroh, Eli; Arti, Dwi Windu Kinanti; Suyanto, Jipri; Setyaningsih, Yuliani (Jurnal Kesehatan Masyarakat, 2024)
The risk of chemical exposure in hospitals is a critical issue in the field of healthcare. Exposure to hazardous chemicals can have a negative impact on the health of healthcare workers operating in hospital environments. Hospitals utilize various chemicals, and exposure can occur through inhalation, ingestion, and skin absorption. This research, conducted in the year 2023, aims to assess the knowledge and attitudes of hospital employees regarding chemical hazards. The research employed a cross-sectional design with a total population sampling technique, with a sample size of 154 employees including doctors, nurses, pharmacists, laboratory technicians, radiologists, and support staff divided into three units: medical services, medical support, and management. Data analysis utilized bivariate analysis and the chi-square test for relationship testing. Multivariate analysis was also employed using logistic regression. The study's results reveal that 63% of the individuals are under 30 years of age, the majority are female (67.5%), 66.2% have less than 3 years of work experience, 62.3% work in medical service units, and 77.3% have an education level of a bachelor's degree or higher. Additionally, 52.6% of the employees are unmarried. A total of 76% of employees exhibit a positive attitude, and 89% possess good knowledge of chemical hazards. The study demonstrates a relationship between individual characteristics (age, gender, work experience, and unit) and the level of knowledge of chemical hazards among hospital employees. The multivariate analysis revealed that age and work unit are the influential variables. This research concludes that the majority of employees at the Dental and Oral Hospital possess good knowledge of chemical hazards and can recognize chemical hazard symbols in accordance with the GHS. Furthermore, most of them exhibit a positive attitude towards preventive measures and understanding of chemical hazards. The data analysis results indicate that there is a relationship between age, length of service, and work unit with the level of chemical hazard knowledge.